2021
DOI: 10.1177/23259671211030495
|View full text |Cite
|
Sign up to set email alerts
|

Acetabular Morphology and Spinopelvic Characteristics: What Predominantly Determines Functional Acetabular Version?

Abstract: Background: In addition to the relative size of the acetabular rim and how the pelvis is positioned in space, the plane in which the acetabular version is calculated also affects its measurement. Purpose: To determine the relative contribution of pelvic and acetabular characteristics on morphological version (measured relative to the anterior pelvic plane angle [APPA]) and functional version (measured relative to the horizontal table). Study Design: Cross-sectional study; Level of evidence, 3. Methods: Include… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(13 citation statements)
references
References 51 publications
(86 reference statements)
1
12
0
Order By: Relevance
“…Very little subsequent work has been done on this relationship, with Tannast et al 10 in 2012 suggesting that acetabular retroversion was caused by the external rotation of the hemipelvis and, more recently, that functional or ‘physiological’ acetabular retroversion was associated primarily with PT angle. 13 This is in keeping with our findings that the radiological signs of acetabular retroversion decreased when the posterior PT increased from the supine to standing positions. Functional acetabular retroversion can be due to a low PT angle.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Very little subsequent work has been done on this relationship, with Tannast et al 10 in 2012 suggesting that acetabular retroversion was caused by the external rotation of the hemipelvis and, more recently, that functional or ‘physiological’ acetabular retroversion was associated primarily with PT angle. 13 This is in keeping with our findings that the radiological signs of acetabular retroversion decreased when the posterior PT increased from the supine to standing positions. Functional acetabular retroversion can be due to a low PT angle.…”
Section: Discussionsupporting
confidence: 91%
“…However, the ischial spine sign suggests that these appearances are partially a feature of external rotation of the hemipelvis, 9,10 and more recent work suggests that in addition to this external rotation deformity, there is some degree of prominence of the iliac wing anteriorly, 11 as well as lower pelvic tilt (PT) angle and external rotation of the iliac wing. 12 Functional acetabular retroversion has been associated with PT, 13 and the effect of PT on the interpretation of radiological parameters, in particular the assessment of acetabular retroversion, has been clearly illustrated. 14,15…”
Section: Introductionmentioning
confidence: 99%
“…Of those, we considered 5% (73 [146 hips]) as potentially eligible as controls based on the absence of major hip osteoarthritis, trauma, or deformity. The asymptomatic group had, partially, been used in a previous study [12], and further selection based on symptoms and daily life functioning was done for the current study. These patients were contacted by telephone or email and answered standardized and validated questionnaires regarding hip and overall function, including the OHS (range 0 to 48) [11,36] and the Patient-Reported Outcome Measurement Information System (PROMIS) general and mental health score (range 0 to 100) [15].…”
Section: Asymptomatic Groupmentioning
confidence: 99%
“…CT with threedimensional (3D) reconstruction allows for better characterization, and it can account for pelvic tilt, rotation, and obliquity [50]. Furthermore, additional characteristics such as the ratio between acetabular cartilage and fossa areas [46] and spinopelvic characteristics, which influence pelvic tilt and acetabular orientation [12,29], are considered important predictors of symptomatic hip disease [22,26,39].…”
Section: Introductionmentioning
confidence: 99%
“…They found that morphological anatomical anteversion is mainly dependent on acetabular morphology and the prominence of anterior and posterior acetabular rims and is only weakly related to pelvic measurements. They also suggested that functional anteversion is more important in determining treatment, as it has been found to be strongly associated with pelvic tilt; assessment of pelvic mobility is very important before deciding the treatment of hip version abnormalities [1]. In this issue of Clinical Orthopaedics and Related Research ® , Verhaegen et al [10] included the patient's activity status, spinopelvic parameters, functional anteversion, and CT measurements; they compared the asymptomatic hips with a symptomatic cohort to try to identify parameters more likely to be associated with painful hips.…”
mentioning
confidence: 99%